Sosialisasi dan Pelatihan Penggunaan Aplikasi SIDOKAR Bagi Kelompok Kerja Dalam Mempersiapkan Akreditasi Rumah Sakit Umum Puri Raharja Denpasar - I Made Satrya Ramayu (Universitas Negeri Gorontalo, 2023)
Hospital accreditation is critical to improving healthcare quality, reducing patient harm, protecting patients, communities, and human resources, and promoting government health initiatives. One of the problems encountered during accreditation was when the surveyor conducted a document audit. The team needed help showing the documents because they needed to be structured appropriately. The large number of documents in the form of hardcopy allows the document to be damaged or lost. The holding of training and socialization of SIDOKAR application-based technology can solve this problem which is expected to help organize and search documents quickly. The methods used in this activity are lectures and mentoring. The conclusion from this activity was that the activity was successfully realized by monitoring how well each working group was prepared to welcome the accreditation survey. In addition, the implementation of socialization and training also shows that the application can assist the working group in increasing the efficiency, effectiveness, and quality of the accreditation preparation process.